A systematic review of interventions for co-occurring substance use and borderline personality disorders - Lee, Nicole; Cameron, J.; Jenner, L. (Wiley-Blackwell Publishing Ltd., 2015)
Issues: The aim of this study was to undertake a systematic review on effective treatment options for co-occurring substance use and borderline personality disorders to examine effective treatments for this group. Approach: A systematic review using a narrative analysis approach was undertaken as there were too few studies within each intervention type to undertake a meta-analysis. The inclusion criteria comprised of English language studies (between 1999 and 2014) and a sample of >70% borderline personality disorder, with measurable outcomes for substance use and borderline personality disorder. All abstracts were screened (n  = 376) resulting in 49 studies assessed for eligibility, with 10 studies, examining three different treatment types, included in the final review. Key Findings: There were four studies that examined dialectical behaviour therapy (DBT), three studies that examined dynamic deconstructive psychotherapy (DDP) and three studies that examined dual-focused schema therapy (DFST). Both DBT and DDP demonstrated reductions in substance use, suicidal/self-harm behaviours and improved treatment retention. DBT also improved global and social functioning. DFST reduced substance use and both DFST and DPP improved treatment utilisation, but no other significant positive changes were noted.Implications: Overall, there were a small number of studies with small sample sizes, so further research is required. However, in the absence of a strong evidence base, there is a critical need to respond to this group with co-occurring borderline personality disorder and substance use. Conclusion: Both DBT and DPP showed some benefit in reducing symptoms, with DBT the preferred option given its superior evidence base with women in particular. [Lee NK, Cameron J, Jenner L. A systematic review of interventions for co-occurring substance use and borderline personality disorders. Drug Alcohol Rev 2015;34:663–672]